Tensions and Trade-offs in Real-World Laboratories – The Participants' Perspective - Franziska Engels; Jan-Christoph Rogge (GAIA - Ecological Perspectives for Science and Society, 2018)
Real-world laboratories have made their way into policy programs and corporate agendas. They are expected to foster innovation on both the local and wider societal scales through co-creative settings in the “real world”. Yet little attention has been paid to how these multiple expectations affect micro-level practices and pose challenges for the heterogeneous actors involved in these settings. Two case studies show the emerging tensions relating to participation, temporality and space, and the ways in which participants perceive and deal with them.
Keywords: 320; participation; real-world laboratories; space; temporality; tensions